The passing-on of price overcharges in European competition damages actions: A matter of causation and an issue of policy - Claudio Lombardi (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
This paper analyses the functioning of the passing-on of price overcharges in damages actions for breaches of EU competition law and aims to give a critical appraisal of the present regulatory framework in Europe. In particular, this paper maintains that the European Directive 2014/104, in order to facilitate the claims of damages caused by the infringement of European competition rules and to provide full compensation for those damages, has adopted a complex set of rules placing the burden of proof on the party that has, assumedly, the best access to evidence on the relevant issue. Moreover, it is noted that these rules give a strict definition of the overcharge harm and of its diffusion through the market chain. In this connection, it is argued that the objectives of the Directive are partly compromised by the fact that this restrictive approach fails to take into consideration a number of other subjects who may potentially be damaged by the passing-on of the overcharge harm. Secondly, this paper maintains that the set of rules laid down by the Directive 2014/104 creates a system of presumptions, which, contrary to its intended purpose, is likely to discourage damages actions. Finally, this paper argues that actions by indirect purchasers based on the passing-on of the overcharge will still need to heavily rely on domestic civil law rules in particular on local principles of causation and evidence.
Keywords: 320; European competition law; damages actions; private enforcement; passing-on; indirect purchaser; passing-on defence; Directive 2014/104; causation; civil liability